Nano Science and Technology - V S Muralidharan (Ane Books Pvt.Ltd., 2009)
"This is a quick and easy guide to the basics of nanoscience and technology. It begins with an introduction to terminology, then delineates various methods of synthesis of metal colloids, clusters polymer supported clusters nano tubes, carbon nano tubes, inorganic nano tubes, nano wires, organic crystals, and nano fibers. The book then presents characterization and standardization, detailing structural elucidation methods, x-ray diffraction and absorption, particle size determination, structure of surfaces, spectroscopy, luminescence and microscopy. It concludes by presenting standards of nano metrology as well as applications of nanoscience and technology."-